Epidemiologic surveillance of canine visceral leishmaniasis in the municipality of Recife, Pernambuco - Filipe Dantas-Torres; Maria Aparecida da Gloria Faustino; Osmar Cavalcanti da Costa Lima; Ridelane Veiga Acioli (Sociedade Brasileira de Medicina Tropical (SBMT), 2005)
This paper describes an epidemiologic investigation carried out in Imbiribeira district, where a canine visceral leishmaniasis case was recorded. Despite the absence of seropositive dogs and sand flies, these findings are not sufficient to discard the occurrence of a zoonotic cycle of visceral leishmaniasis in Recife.